Inserção laboral das pessoas com deficiência no Sistema S da cidade de São Carlos - Santos, Allyne Cristina dos (2018)
Since 1950 people with disabilities have been inserted into the labor market. From that decade, much was done for the inclusion of these people, laws were created so that their rights could be guaranteed. So that the companies these laws will be fulfilled only to avoid penalties provided for failure to comply with them. In fact, the work of the disabled person must be achieved by their own commitment and conceived by society, by the competence and not because the legislation has preserved it in a charitable way, a percentage of vacancies, which contributes to the spread of stigma. In accordance with the above, the following questions arose: How was the insertion of people with disabilities into the labor market? What are the working conditions of these people? What are the reasons for hiring disabled workers? The present study aimed to analyze how people with disabilities were inserted in the professional environment, as workers, in the institutions of System S in the city of São Carlos. This research has a qualitative and descriptive character, in the case study modality and was developed in the institutions of System S of the city of São Carlos. The sample was composed of 12 employees with disabilities and 2 responsible for the institutions of System S. The data was processed through Content Analysis. The results obtained by the study, we can understand that the employees with deficiency inserted in the institutions of System S are, for the most part, satisfied with the working conditions. Regarding these institutions, there is a concern to provide adequate conditions for employees with disabilities to perform their work adequately, valuing their capabilities and potential.